Expressão da tetraspanina (CD81) em mieloblastos e sua associação com o perfil de citocinas Th2 e prognóstico adverso em leucemia mielóide aguda - SOARES, Rossy-Eric Pereira (2021)
CD81, a member of the testraspanin family, is a membrane protein involved in immunosuppressive responses and associated with adverse outcomes in multiple myeloma and acute myoid leukemia (AML). Although studies support the occurrence of dysregulation in the production of cytokines in hematologic malignancies, the relationship between the expression of CD81 in myeloblasts and the cytokine profile in patients with AML is not known. Thus, we evaluated the association between CD81 expression and Th1, Th2 and Th17 cytokine levels, as well as its prognostic value in AML. For this, 121 patients diagnosed with AML and 40 control subjects were studied. We observed the expression of CD81 in 100/121 (82.6%) patients (P<0.05). Serum levels of IL-2, IL-4, IL-10, TNFα and IFNγ were significantly higher in AML patients compared to the control group (P<0.05). The expression of CD81, associated with low levels of IL 2 and IFNγ and high levels of IL-4 and IL-10, negatively affected overall survival, event free survival and contributed to early relapse. Furthermore, we demonstrated, through principal component analysis, that there is a segregation between groups with the lowest and highest percentage of blasts expressing CD81 (P<0.05) for IL-2, IL-10, IFNγ and overall survival. In summary, we confirm that CD81 is a poor prognostic marker for AML, possibly because its expression present in a higher frequency of blasts is associated with an immunosuppressive immune response profile. Furthermore, we demonstrated that this tetraspanin is capable of separating risk groups not only due to the presence or absence of expression, but mainly due to the frequency with which the blasts present expression of this antigen. Finally, our findings contribute to the understanding of the relationship of CD81 expression with the immune response in patients with AML and to expand investigations into the role of this tetraspania in this neoplasm, in addition, of course, highlighting it as a useful marker to predict prognosis and possibly, candidate for target therapy.